Educational Collaboration : Teachers and Artificial Intelligence - Mujiono Mujiono (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to analyze the collaboration between teachers and Artificial Intelligence that can meet the needs and goals of better education. This study uses a qualitative descriptive method with a literature review research design by collecting information from reputable international journal articles indexed in Scopus over the last five years (2018-2023) using the Publish or Perish search tool. The process of meta-analysis in this research begins with formulating the research question, andthen collecting relevant literature data that aligns with the research question. Next, the data is prepared by evaluating the literature's relevance to the research topic. Afterwards, the data from the selected literature is analyzed and synthesized. The results show that collaboration between teachers and Artificial Intelligence can be a good solution to improve learning effectiveness and help students learn in a personalized way. Although Artificial Intelligence technology can assist teachers in the learning process, teachers still play an important role in guiding and inspiring students. Therefore, collaboration between teachers and Artificial Intelligence technology should also be done carefully and directed towards improving a better and more meaningful learning experience for students.